Geographic variation in shoot structure in association with fruit size in an evergreen woody species. Issue 3 (7th May 2021) - Goto, Takuma; Osada, Noriyuki
Abstract: The generality of scaling relationships between multiple shoot traits, known as Corner's rules, has been considered to reflect the biomechanical limits to trees and tree organs among the species of different leaf sizes. Variation in fruit size within species would also be expected to affect shoot structure by changing the mechanical and hydraulic stresses caused by the mass and water requirement of fruits. We investigated the differences in shoot structure and their relationship with fruit size in Camellia japonica from 12 sites in a wide geographic range in Japan. This species is known to produce larger fruits with thicker pericarps in more southern populations because warmer climates induce more intensive arms race between the fruit size and the rostrum length of its obligate seed predator. We found that, in association with the change in fruit size, the diameter and mass of 1-year-old stems were negatively associated with latitude, but the total mass and area of 1-year-old leaves did not change with latitude. Consequently, the length of 1-year-old stems and the total mass and area of 1-year-old leaves at a given stem diameter were positively associated with latitude in the allometric relationships. In contrast, the allometric relationships between stem diameter and total mass of the 1-year-old shoot complex (the leaves, stems and fruits that were supported by a 1-year-old stem) did not differ across the trees of different latitudes. Thus, natural selection on fruit size is considered to influence the other traits of Corner's rules in C. japonica, but all of the traits of Corner's rules do not necessarily change in a similar manner across latitudinal gradients. Abstract : Camellia japonica is known to produce larger fruits in more southern populations because of intensive arms race between the fruit size and the rostrum length of its obligate seed predator. We found that such geographic changes in fruit size resulted in thicker 1-year-old stems in more southern populations to withstand the loads and/or water requirements of fruits. Such patterns were constrained by the allometric relationships between stem diameter and total mass of the 1-year-old shoot complex (the leaves, stems and fruits that were supported by a 1-year-old stem), which did not differ across the trees of different latitudes.